DIRECT ASSIMILATION OF ATMOSPHERIC CARBON BY IMMATURE APPLE FRUITS. Issue 13 (9th September 2022) - Imada, Shogo; Tako, Yasuhiro; Moriya, Yuki
Abstract: Although fruit development primarily depends on photoassimilation by leaves, immature green fruits can also directly assimilate atmospheric CO2 . To elucidate the process of C accumulation due to direct assimilation by fruit, we conducted a 13 CO2 exposure experiment in an orchard in late June with immature 'Fuji' apples ( Malus domestica ). Four fruits from three trees were enclosed in transparent plastic bags and exposed to 13 CO2 using an in-situ exposure system. Fruits were collected prior to and immediately following exposure in early July, late September and mid-November, and 13 C concentrations in the peduncle, skin, flesh and core (including seeds) were measured. The higher assimilated 13 C concentrations measured following exposure indicated that the fruits directly assimilated atmospheric 13 C. The 13 C concentration in fruit skin was higher immediately after exposure and in early July compared with that prior to exposure. In late September and mid-November, 13 C concentrations were close to natural levels.